Pengaruh Sikap Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Pada Kantor Bea Dan Cukai Belawan - Syafitri, Desy; Supriadi, Supriadi; Julkarnain, Julkarnain; Elny, Hj. Sri; Nasti, Nilawati (Manajemen dan Bisnis, 2024)
This research aims to analyze the influence of work attitudes and leadership styles on employee performance at the Belawan Customs and Excise Office. A positive work attitude and effective leadership style are considered key factors in improving employee performance in an office environment. The research method uses a quantitative approach by distributing questionnaires to employees at the Belawan Customs and Excise Office. Data analysis was carried out using descriptive statistical techniques and regression to measure the relationship between work attitude variables, leadership style and employee performance. The research results show that a positive work attitude has a significant influence on employee performance. Apart from that, an effective leadership style also has a positive contribution to employee performance at the Belawan Customs and Excise Office. These findings provide further understanding about the importance of creating a Leadership Style that supports positive work attitudes and implementing an effective leadership style to increase employee productivity and quality of performance. The recommendations of this research include the need to develop training programs to increase positive work attitudes and promote supportive leadership styles in the Belawan Customs and Excise Office Leadership Style. In addition, further research can be conducted to explore additional factors that may influence employee performance